2007
DOI: 10.1111/j.0014-3820.2001.tb00782.x
|View full text |Cite
|
Sign up to set email alerts
|

Vestigial Organs as Opportunities for Functional Innovation: The Example of the Penstemon Staminode

Abstract: Abstract. Vestigial organs arise commonly during morphological evolution, but they need not be destined for elimination. Instead, vestigial organs may facilitate functional innovation because their freedom from functional constraints allows them to assume novel roles that their functional progenitor could not perform. We illustrate this vestigial transition between functions with an experimental study of the staminode of Penstemon flowers. Previous phylogenetic and developmental studies indicate that this stam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…1b) and would be the first scented tissue encountered by a visitor at the flower opening. Despite the importance of staminodes in the reproductive ecology of Penstemon and similar bilabiate flowers (Dieringer and Cabrera 2002;Walker-Larsen and Harder 2001), staminode scents are known only from one other species, Jacaranda oxyphylla (Guimarães et al 2008). A previous study identified a mechanical function for the P. digitalis staminode, to ensure that bee bodies contact the sexual parts of the flower (Dieringer and Cabrera 2002).…”
Section: Discussionmentioning
confidence: 99%
“…1b) and would be the first scented tissue encountered by a visitor at the flower opening. Despite the importance of staminodes in the reproductive ecology of Penstemon and similar bilabiate flowers (Dieringer and Cabrera 2002;Walker-Larsen and Harder 2001), staminode scents are known only from one other species, Jacaranda oxyphylla (Guimarães et al 2008). A previous study identified a mechanical function for the P. digitalis staminode, to ensure that bee bodies contact the sexual parts of the flower (Dieringer and Cabrera 2002).…”
Section: Discussionmentioning
confidence: 99%
“…4). The staminodes may hinder easy access to the nectaries and increase the visit duration of bumblebees and the chance of contact with the three stamens (Torchio 1974;Walker-Larsen and Harder 2001), although this possibility remains to be examined experimentally.…”
Section: Visitors and Visitation Frequencymentioning
confidence: 99%
“…Indeed, once a body part loses functionality following a change in lifestyle, it will degenerate in a neutral manner, and this neutral evolution makes it prone to assume new functions. To our knowledge, however, very few examples have been described yet (1,4).…”
mentioning
confidence: 99%